Effectiveness of WhatsApp as an academic tutoring tool in the academic performance of university students - Valero-Ancco, Vidnay Noel; Calderon-Quino, Katty Maribel; Bustinza-Choquehuanca, Sonia Agley (Edelweiss Applied Science and Technology, 2024)
The use of WhatsApp has emerged as a crucial tool in the academic field, especially among university students, where its influence on academic performance is a topic of growing interest. This article aims to demonstrate how WhatsApp influences academic performance through academic tutoring in university students. The study sample consisted of 167 university students from three professional programs. Three research instruments were applied: an initial questionnaire, a satisfaction survey, and a grade record. The results reveal that the effective use of WhatsApp in academic tutoring offers advantages such as effective communication between peers and tutor, versatility in sharing files, and carrying out various group activities such as messaging, video calls, and conference calls. However, disadvantages were also evident, such as the distraction the app can cause when students do not manage their time properly or engage in non-academic activities. In conclusion, it is established that the use of WhatsApp in academic tutoring positively influences the academic performance of university students, demonstrating that its integration into educational processes can enhance communication and academic support, which has significant implications for educational practice and the development of more effective teaching strategies.